Peran Lembaga Penjamin Simpanan dalam Menjaga Stabilitas Sektor Perbankan di Indonesia: Systematic Literature Review - Suhardiono, Suhardiono; Sembel, Roy; Suwandi, Suwandi (Universitas Batanghari Jambi, 2025)
This study aims to understand the role of the Deposit Insurance Corporation (LPS) in maintaining the stability of the banking sector in Indonesia through a systematic literature review methodology. This study analyzes 12 articles identified from the Emerald and Elsevier databases using the keywords